Surgical protocol of robotic liver resection using a two-surgeon technique (TAKUMI-3): a technical note and initial outcomes - Kosei Takagi; Tomokazu Fuji; Kazuya Yasui; Yuzo Umeda; Motohiko Yamada; Takeyoshi Nishiyama; Yasuo Nagai; Noriyuki Kanehira; Toshiyoshi Fujiwara (World Journal of Surgical Oncology)
Abstract Background Internationally, evidence supporting robotic liver resection (RLR) has gradually increased in recent years. However, a standardized protocol for RLR remains lacking. This study describes a surgical protocol and the initial outcomes of RLR in a high-volume center for robotic hepatopancreatobiliary surgery in Japan. Methods Patients were placed in the reverse Trendelenburg position, with a supine position for anterolateral tumors and left lateral position for posterosuperior tumors. Our standard RLR protocol involved a two-surgeon technique. Liver parenchymal transection was performed by an assistant using the clamp crush technique with a console, with or without a laparoscopic Cavitron ultrasonic surgical aspirator (CUSA). Surgical techniques, including the tips, tricks, and pitfalls of RLR, are also demonstrated. Results We performed 113 RLR at our institution for common primary diseases, including hepatocellular carcinoma (n = 52, 46.0%) and metastatic tumors (n = 48, 42.5%) between July 2022 and December 2024. The median operative time and estimated blood loss were 156 min (interquartile range [IQR], 121–209 min) and 20 mL (IQR, 0–100 mL), respectively. During liver parenchymal transection, a laparoscopic CUSA was used in 59 patients (52.2%), and a water-jet scalpel was used in 12 patients (10.6%). The incidence of mortality, major complications, and bile leakage was 0%, 6.2%, and 2.7%, respectively. The median hospital stay was 7 days (IQR, 6–9 days). Conclusions We successfully introduced an RLR program using the two-surgeon technique. Safe implementation of RLR can be achieved upon completion of the training program and thorough understanding of the surgical protocols.